Linguistic cues of deception in Malaysian online investment scams’ promotional materials - Ameiruel Azwan Ab Aziz,; Nurul Atiqah Mohd Sharif,; Wan Farah Wani Wan Fakhruddin,; Amirah Mohd Juned,; Nursyaidatul Kamar Md Shah,; Ariff Imran Anuar Yatim,; Aminabibi Saidalvi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The entire world has transitioned to a borderless information flow in this high-technology era, making communication more effective at the ease of the fingertips. However, these advantages come with various cybercrimes that can easily mislead readers and win them over to their point of view, including online investment scams. This quantitative study aims to analyse the linguistic cues of deception of investment scams’ promotional materials using the Linguistic Inquiry and Word Count (LIWC) and Statistical Package for Social Science (SPSS) software. The data was gleaned from official website pages of investment scams provided by the Royal Malaysia Police (RMP), Central Bank of Malaysia (CBM), Financial Consumer Alert List (FCA), and the Securities Commission Malaysia (SC). Descriptive analysis and Pearson correlation analysis were conducted. The findings of the descriptive analysis show that the highest linguistic cue used in the online investment scam is Lifestyle. For Pearson correlation analysis, the findings show that linguistic cue for Perception significantly correlates with other linguistic cues such as Lifestyle, Social Process, Cognition, and Affect. This indicates that the linguistic cues used in online investment scams are related. The findings of the study can be used as a guide to prevent online investment scam problems in the future.